Pengukuran Laba Berdasarkan Praktik Akuntansi UMKM Online di Kabupaten Pamekasan - Fena Ulfa Aulia - (Akuntansi : Jurnal Akuntansi Integratif, 2020)
ABSTRACT A business entity must be separate from the private entity in order to measure its performance. Most of the UMKMs in Pamekasan have not yet separated their personal and business entities, so the measurement of earnings is biased. Nowadays, the SMEs in Pamekasan have utilized online facilities in their sales both through online shops and social media. When referring to the birth of accounting, accounting practices are born from business practices, so that changing conventional business practices online also changes accounting practices. This research is a qualitative descriptive study using primary data through interviewing correspondents with data analysis techniques describing data and discussed based on existing theories then conclusions are drawn. The population in this study is all online MSMEs in Pamekasan with random sampling techniques with regard to the principle of convenience as many as 10 samples. The results of this study indicate that there are various online MSME earnings measurements with varied accounting practices and are still simple and do not yet refer to SAK EMKM.